2020
DOI: 10.30574/gscbps.2020.13.2.0365
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of entomofauna associated with crop of okra (Abelmoschus esculentus) and assessment of damage caused by insect pests in Man, west of Côte d'Ivoire

Abstract: Okra (Abelmoschus esculentus) is one vegetable crops most cultivated in Côte d'Ivoire. However, the plant is attacked by insects which caused important damage. This study was carried out to inventory entomofauna associated with okra crop and assess the damage caused by the pests. The insects were captured using pliers, sweep net by mowing technique and colored traps. Overall, a total of 61 species belonging to 36 families grouped into 10 orders were identified. During the plant cycle, 11602 insects were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It is necessary to find effective control methods that do not harm human health and the environment. In Côte d'Ivoire, Yao et al (2020) observed a reduvid bug, Rhynocoris rapax (Stal) as a predator of P. decolorata. This study evaluates the bioecological parameters of R. rapax.…”
mentioning
confidence: 99%
“…It is necessary to find effective control methods that do not harm human health and the environment. In Côte d'Ivoire, Yao et al (2020) observed a reduvid bug, Rhynocoris rapax (Stal) as a predator of P. decolorata. This study evaluates the bioecological parameters of R. rapax.…”
mentioning
confidence: 99%